2012
DOI: 10.1590/s0101-60832012000600002
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese validation of the children's eating attitudes test

Abstract: Background: The Eating Attitudes Test (EAT) is the most widely used instrument for evaluating eating disorders in adults and adolescents in a variety of cultures and samples. Objective: The aim of this study was to analyse the psychometric properties of the Portuguese version of the Children's Eating Attitudes Test (ChEAT). Method: Nine hundred and fifty-six Portuguese secondary students (565 girls and 391 boys) answered the ChEAT. The test-retest reliability was obtained with data from 206 participants from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…17 The ChEAT is rated on a Likert-type scale from 1 (never) to 6 (always). The most symptomatic response is recoded into a score of 3 (always), 2 (usually), or 1 (often).…”
Section: Children Eating Attitudes Test (Cheat)mentioning
confidence: 99%
“…17 The ChEAT is rated on a Likert-type scale from 1 (never) to 6 (always). The most symptomatic response is recoded into a score of 3 (always), 2 (usually), or 1 (often).…”
Section: Children Eating Attitudes Test (Cheat)mentioning
confidence: 99%
“…However, sex differences are not a likely explanation; we fit the 5-factor model in boys and girls separately and found the global fit and factor loadings were very similar. Other studies also found only trivial differences in their measurement models when estimated separately for girls and boys (e.g., Teixeira et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…between the ages of 8 and 14(Ambrosi-Randi c & Pokrajac-Bulian, 2005;Chiba et al, 2016;De León, del Consuelo, Ruiz, & Jaime, 2008; Elizathe, Murawski, Arana, & Rutsztein, 2012; Maïano, Morin, Lanfranchi, & Therme, 2013; McEnery, Fitzgerald, McNicholas, & Dooley, 2016; Pilecki, Kowal, Woronkowicz, Kryst, & Sobiecki, 2013; Ranzenhofer et al, 2008; Rojo-Moreno et al, 2011; Sancho, Asorey, Arija, & Canals, 2005; Senra, Seoane, Vilas, & Sánchez-Cao, 2007;Teixeira et al, 2012;Theuwis, Moens, & Braet, 2009). Study characteristics and principal components analysis (PCA) or factor analysis (FA) results fromAnton, Han, et al (2006),Lynch and Eppers-Reynolds (2005), and the 13 new studies are summarized in Supporting Information Table S1, alongside the seminal Garner…”
mentioning
confidence: 99%
“…Children's Eating Attitudes Test. 46,47 Children's Eating Attitudes Test (ChEAT) assesses problematic eating attitudes and behaviors through 26 items answered on a 6-point point Likert scale (1 = never; 6 = always). For the purpose of this study, only the total score was used (McDonald's o for this sample = 0.91).…”
Section: Child Self-report Measuresmentioning
confidence: 99%